Nutritional quality of palm fat substituted chicken nuggets - Alina A.R.; Babji A.S.; Affandi S. (2024)
Purpose: The purpose of this paper is to improve the nutritional value of chicken nuggets by partial substitution of animal fat with palm stearin. Three nugget formulations with the fat level of 10.3 per cent palm fats consisted of blends from Olein: Stearin at ratios of 30:70, 50:50, 70:30 were used to replace chicken skin (control). Palm fat treatments resulted in a significant decrease of cholesterol content. Design/methodology/approach: Four nugget formulations with the fat level of 10.3 per cent palm fats consisting of blends from Olein: Stearin at ratio of 30:70, 50:50, 70:30 and a commercial shortening, Socfat 36 are studied. The same formulation using chicken skin as a control and a commercial brand of nugget is used as a comparison. Proximate analysis of raw and cooked palm fat nuggets showed a decrease in the protein content and an increase of the fat content. The cholesterol content were reduced up to 45.9 per cent through the addition of palm fat, when compared against the control treatment. Fatty acid composition of palm fats in the palm substituted formulations increased the level of C16:0 and decreased C16:1, C18:1, C18:2, compared with fat from chicken skin. Findings: The cholesterol content was reduced by 45.9 per cent when chicken skin and fat were substituted with palm fats. The texture of chicken nugget increased when added with palm fats. Palmitic acid (C16:0) content increased while palmitoleic acid (C16:1), oleic (C18:1) and linoleic acid (C18:2) decreased in palm fat treated nuggets. Originality/value: The paper is of value in showing how palm stearin and olein usage in chicken nuggets helps reduce the product's cholesterol content. Emerald Group Publishing Limited.